2021
DOI: 10.1111/gcb.15505
|View full text |Cite
|
Sign up to set email alerts
|

Winter snow and spring temperature have differential effects on vegetation phenology and productivity across Arctic plant communities

Abstract: Tundra dominates two‐thirds of the unglaciated, terrestrial Arctic. Although this region has experienced rapid and widespread changes in vegetation phenology and productivity over the last several decades, the specific climatic drivers responsible for this change remain poorly understood. Here we quantified the effect of winter snowpack and early spring temperature conditions on growing season vegetation phenology (timing of the start, peak, and end of the growing season) and productivity of the dominant tundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
62
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 107 publications
7
62
0
1
Order By: Relevance
“…However, at the population level C . aeneicollis populations are negatively impacted by dry years (Dahlhoff et al, 2019), consistent with a role for interannual variation in cold stress impacting population dynamics (although it remains possible that population declines are driven by the impacts of snow on soil water content, microbial respiration, and primary productivity; Kelsey et al, 2021). We conclude that there is good evidence that interannual variation in snow cover can impact fitness of ectotherms that overwinter in the soil, but more research is required to fully demonstrate the mechanisms.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…However, at the population level C . aeneicollis populations are negatively impacted by dry years (Dahlhoff et al, 2019), consistent with a role for interannual variation in cold stress impacting population dynamics (although it remains possible that population declines are driven by the impacts of snow on soil water content, microbial respiration, and primary productivity; Kelsey et al, 2021). We conclude that there is good evidence that interannual variation in snow cover can impact fitness of ectotherms that overwinter in the soil, but more research is required to fully demonstrate the mechanisms.…”
Section: Discussionmentioning
confidence: 64%
“…Climate change-induced reductions in snow cover will therefore have very different fitness implications for organisms living at different elevations, and these fitness impacts cannot be predicted based on air temperatures alone. This highlights the importance of refining our understanding of how snow interacts with air and soil temperatures to determine organismal performance and fitness, in order to predict the biological impacts of climate change (Fitzpatrick et al, 2019(Fitzpatrick et al, , 2020Kearney, 2020;Kelsey et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative ability of temperature accumulation and snow melt timing to predict spring phenology in high‐elevation and high‐latitude environments appears to vary among species as well as between phenological stages (Kelsey et al, 2020; Quaglia et al, 2020; Theobald et al, 2017; Wipf, 2010). Following this, we found that temperature accumulation did cue phenology (in tandem with other drivers) for some, but not all species and not all responses.…”
Section: Discussionmentioning
confidence: 99%
“…As warming progresses, mid and high latitudes may begin to experience similar trends to those that we found in Mexico at lower latitudes. The persistence of glaciers and snowpack at the highest elevations or latitudes may buffer habitats from warming-induced stress during the growing season, at least temporarily ( 50 ). In other systems, these buffering effects have resulted in lagged responses of plant community composition and productivity to climate change ( 51 ).…”
Section: Discussionmentioning
confidence: 99%